2016
DOI: 10.2106/jbjs.cc.15.00260
|View full text |Cite
|
Sign up to set email alerts
|

Emphysematous Septic Arthritis of the Knee Caused by Citrobacter freundii

Abstract: The constellation of signs, symptoms, and radiographic features was characteristic of emphysematous septic arthritis. The patient recovered well following surgery and treatment with antibiotics. To our knowledge, this is the first reported case of such arthritis caused by C. freundii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a 50-year-old diabetic woman, Nemade et al . 21 reported emphysematous septic arthritis of the knee caused by C. freundii . Pant et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 50-year-old diabetic woman, Nemade et al . 21 reported emphysematous septic arthritis of the knee caused by C. freundii . Pant et al .…”
Section: Discussionmentioning
confidence: 99%
“…C. freundii is a formidable pathogen, and research has shown that a significant number of isolates frequently exhibit drug resistance 28 , 29 . Because of the variety of susceptibility patterns and the high prevalence of drug resistance, tailored treatment for each patient based on culture and sensitivity testing is advised 21 . Our patient was treated accordingly Figures 3 , 4 .…”
Section: Discussionmentioning
confidence: 99%